Difficulty classifications of laparoscopic repeated liver resection in patients with recurrent hepatocellular carcinoma. Issue 3 (13th August 2019) - Kinoshita, Masahiko; Kanazawa, Akishige; Kodai, Shintaro; Shimizu, Sadatoshi; Murata, Akihiro; Nishio, Kohei; Hamano, Genya; Shinkawa, Hiroji; Tanaka, Shogo; Takemura, Shigekazu; Tsukamoto, Tadashi; Kubo, Shoji
Abstract: Introduction: This study aimed to investigate the predictive factors and classifications for difficulty of laparoscopic repeated liver resection (LRLR) in patients with recurrent hepatocellular carcinoma. Methods: Sixty patients who underwent LRLR were included. Potential predictive factors for difficult LRLR included the approach of the previous liver resection (laparoscopic or open), the number of previous liver resections, a history of cholecystectomy in previous liver resection, the operative procedure of previous liver resection, whether the tumor was near the resected site of the previous liver resection, non‐surgical treatments before the present surgery, and the difficulty scoring system for laparoscopic liver resection. The relationship between these factors and perioperative outcomes were evaluated to investigate the predictive factor for difficult LRLR. Results: Univariate and multivariate analyses demonstrated that an open approach during previous liver resection, two or more previous liver resections, a history of previous liver resection with not less than sectionectomy, tumor near the resected site of the previous liver resection, and intermediate or high difficulty in the difficulty scoring system were independent risk factors for prolonged operative time and/or severe adhesion of LRLR. Three difficulty classifications were then suggested based on the number of these five predictive factors. The difficulty classification reflected operative time, intraoperative blood loss, and incidence of postoperative complication. Conclusion: The difficulty of LRLR may be predicted by three difficulty classifications using five preoperative predictive factors.